Front Cover: Spherical nucleic acids: Organized nucleotide aggregates as versatile nanomedicine. Issue 1 (22nd February 2022) - Song, Yangmeihui; Song, Wenyu; Lan, Xiaoli; Cai, Weibo; Jiang, Dawei
Abstract : Spherical nucleic acids (SNAs) are oligonucleotide aggregates densely arranged on the surface of nanoparticle core. These organized nucleotide aggregates present significantly different biological properties compared to their linear counterparts, enabling advances in biosensing, bioimaging, and biomedicine. This review provides a comprehensive summary of SNAs and update our current understanding of SNAs for disease diagnosis and treatment. ( Aggregate . e120 )